English translation and classical reception : towards a new literary history - Gillespie, Stuart, 1958-; Wiley InterScience (Online service) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
English Translation and Classical Reception is the first genuine cross-disciplinary study bringing English literary history to bear on questions about the reception of classical literary texts, and vice versa. The text draws on the author's exhaustive knowledge of the subject from the early Renaissance to the present. The first book-length study of English translation as a topic in classical reception Draws on the author's exhaustive knowledge of English literary translation from the early Renaissance to the presentArgues for a remapping of English literary history which would take proper acco.
Making the classics belong: a historical introduction -- Creative translation -- English Renaissance poets and the translating tradition -- Two-way reception: Shakespeare's influence on Plutarch -- Transformative translation: Dryden's Horatian ode -- Statius and the aesthetics of eighteenth-century poetry -- Classical translation and the formation of the English literary canon -- Evidence for an alternative history: manuscript translations of the long eighteenth century -- Receiving Wordsworth, receiving Juvenal: Wordsworth's suppressed eighth satire -- The persistence of translations: Lucretius in the nineteenth century -- Oddity and struggling dumbness: Ted Hughes's Homer.
Includes bibliographical references and index.
Print version record.
Keywords: Classical literature -- Translations into English -- History and criticism; Classical literature -- Appreciation -- Great Britain -- History; English literature -- Classical influences; Translating and interpreting -- Great Britain -- History; Classical literature -- Appreciation -- Great Britain -- History; Classical literature -- Translations into English -- History and criticism; English literature -- Classical influences; Translating and interpreting -- Great Britain -- History; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Classical literature -- Appreciation; Classical literature -- Translations into English; English literature -- Classical influences; Translating and interpreting; Great Britain; Electronic books; Criticism, interpretation, etc; History